Effects of a growth promoter on bean (Phaseolus vulgaris L.) crops in Sancti Spíritus province, Cuba (2017)
In order to evaluate the effect of a growth promoter on the productivity performance and seed-quality in bean (Phaseolus vulgaris L.) crops, two experiments were carried out, one in the field and under controlled conditions. In the field experiments, a Latin square design was used for four treatments as follows: control, 0.5, 0.8 and 1.0 l.ha-1, respectively, where yield components were evaluated. The seeds used in the controlled conditions experiment were from prior trials, in a totally randomized design, at the dosages above mentioned. Seed germination and seedling growth were evaluated. In the field experiments, the product had a stimulating effect on the production. The highest yields were reached with the 0.8 and 1.0 l.ha-1 dosages in number 1, with values of 3.09 and 3.02 t.ha-1, and in number 2, the treatment with the best results was 1.0 l.ha-1, with a yield of 2.07 t.ha-1. In germination, there were significant differences among variables only in the first assessment at three days after planting. The best performance in seedling growth and in dry matter production was the treatment with seeds from the 0.5 l.ha-1 dosage in experiment 1. In addition, in number 2, performance among variables was similar. Therefore, VIUSID agro improved the bean yield performance and did not affect later seed germination nor initial seedling growth.